PENERAPAN METODE SERVQUAL DAN KAIZEN DALAM STRATEGI PERBAIKAN KUALITAS LAYANAN PERBANKAN - Aulia Rizky; Anita Christine Sembiring (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the service quality of PT Bank XYZ and to formulate continuous service improvement strategies using the SERVQUAL method and the Kaizen approach. The research employs a quantitative descriptive method, with data collected through questionnaires distributed to 100 customers. The SERVQUAL analysis is used to measure the gap between customer perceptions and expectations across five service quality dimensions: tangible, reliability, responsiveness, assurance, and empathy. The results show that all service quality dimensions have positive gap values, indicating that the services provided have met and even exceeded customer expectations. The assurance dimension has the highest gap value (0.64), followed by reliability (0.54), empathy (0.47), tangible (0.43), and responsiveness (0.40). Although the overall service quality is considered good, there are still aspects that require improvement, particularly in service assurance and personalized attention to customers. Through the Kaizen approach, service quality improvements are carried out continuously by focusing on process enhancement and the involvement of all organizational elements. Therefore, the implementation of SERVQUAL and Kaizen is expected to help PT Bank XYZ maintain and consistently improve service quality in a sustainable manner.